Gambaran Produksi Komponen Darah di UDD PMI Kabupaten Bojonegoro, Trenggalek dan Jombang - Ardi Panggayuh; Ni Luh Putu Eka Sudiwati; Nia Lukita Ariani; Sri Mudayatiningsih; Atik Kurniawati; Ekowati Retnaningtyas; Budi Susatia (HB PRESS, 2026)
Blood component production is an act of separating donor blood components through certain methods into usable blood components, such as WB (Whole Blood), PRC (Packed Red Cells), FFP (Fresh Frozen Plasma), and TC (Thrombocyte Concentrate). The decline in blood component production requires optimal monitoring between blood stock availability and patient needs so as not to become an obstacle in the transfusion service process. This study aims to determine the description of blood component production at the PMI UDD in Bojonegoro, Trenggalek, and Jombang Regencies for the period of 2024. This study uses a quantitative descriptive design with secondary data sourced from SIMDONDAR. The study sample includes all blood component production at the PMI UDD in Bojonegoro, Trenggalek, and Jombang Regencies for the period of 2024. Using a total sampling technique. Data were recorded using a tally sheet instrument and analyzed using a percentage analysis technique. This study shows that the blood component production results at the PMI UDD in Bojonegoro, Trenggalek, and Jombang Regencies in 2024 were 31,707, 8,643, and 26,485 blood bags, respectively. Most of them produced PRC blood components, respectively, amounting to 22,745 (71.73%), 6,951 (80.42%), and 17,238 (65.09%) blood bags per year. Conclusion: PRC is the most produced blood component.